The Practice of the Division of Labor System in the Government Organization of the Awangpone District Office, Bone Regency - M. Awaluddin A. (Program Pascasarjana Universitas Negeri Makassar, 2023)
The division of labor is not solely based on gender. On this basis, in the division of labor system, the placement of employees must be in accordance with their educational background and skills to support the work process in carrying out their duties and responsibilities. This study aims to determine the system of division of labor in government organizations in Bone Regency and to find out the practice of division of labor at the Awangpone District office with differences in the practice of division of labor at the Awangpone District office with regulations issued by the Bone regent. This writing uses a qualitative approach. Qualitative writing aims to reveal qualitative information so that it puts more emphasis on process issues and meaning by describing a problem. Writing location is a place or area where writing will be done. The place where the writer will write is located at the Awangpone District Office, Bone Regency. In this writing, data sources can be obtained based on facts in the field and the rest is supplemented by existing documents in the field. Most of the employees at the Awangpone sub-district office also do not know the authority and work performance that must be achieved so that this has an impact on unsatisfactory work performance, in terms of coordination it is also still lacking so that cooperation cannot run well in carrying out its functions as an organizer general government affairs at the sub-district level, several positions that are displayed on the organizational structure in Awangpone Sub-district also still appear empty or have not been filled, this indicates that there are several divisions of labor that will be delegated to other sections outside of their duties so that they can be resolved.